Revitalization of Gasing Lingga Folk Game as an Effort to Preserve Cultural Values Based on Local Wisdom in Daik Village, Lingga District - Novang Cahya Sri Kartini; Fahriana Nur Anita; Devi Ratna Fitriani (Faculty of Social and Political Science Universitas Maritim Raja Ali Haji, Indonesia, 2023)
Technological advancements and globalization in Indonesia have had various impacts on people's lives, both positive and negative. This paper aims to analyze efforts to revitalize the Gasing Lingga Folk Game as a means of preserving the cultural values based on local wisdom in Daik Village, Lingga District. The method used in this study is qualitative descriptive. The community, government, and several institutions in Daik Lingga have made efforts to maintain this game. Playing gasing has several benefits, including physical training and improved concentration when played early on. However, efforts to revitalize Lingga's gasing folk games are hindered by several obstacles, such as lack of budget, uneven socialization, technological advancements, and the influence of globalization.